Structural Insights Into TDP-43 and Effects of Post-translational Modifications - François-Moutal, Liberty; Perez-Miller, Samantha; Scott, David D.; Miranda, Victor G.; Mollasalehi, Niloufar; Khanna, May (Frontiers in Molecular Neuroscience, 2019)
Transactive response DNA binding protein (TDP-43) is a key player in neurodegenerative diseases. In this review, we have gathered and presented structural information on the different regions of TDP-43 with high resolution structures available. A thorough understanding of TDP-43 structure, effect of modifications, aggregation and sites of localization is necessary as we develop therapeutic strategies targeting TDP-43 for neurodegenerative diseases. We discuss how different domains as well as post-translational modification may influence TDP-43 overall structure, aggregation and droplet formation. The primary aim of the review is to utilize structural insights as we develop an understanding of the deleterious behavior of TDP-43 and highlight locations of established and proposed post-translation modifications. TDP-43 structure and effect on localization is paralleled by many RNA-binding proteins and this review serves as an example of how structure may be modulated by numerous compounding elements.